Sistem Pemantauan Pembayaran Piutang Nasabah Berbasis Website Pada PT. Guna Artha Kencana - Ni Putu Divta Yuni Sami Asih; Eddy Muntina Dharma; Ni Made Estiyanti (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2020)
This study aims to find out how Website Based Customer Accounts Receivable Monitoring System at PT. Guna Artha Kencana. This study uses a qualitative research approach, the subject of this research id Debt Payment Monitoring System at PT. Guna Artha Kencana. The object of this research is the financial manajer of PT. Guna Artha Kencana. The method used in this research is the Linear Sequential Model, the data collection method used is interviews to obtain primary data and literature studies to obtain secondary data and to design using the Laravel Framework and PHP programming. The results of this research are successful in designing a system for controlling customer receivables payments where this system can be used to record and process every transaction that occurs in the company and this system can also be used to monitor the status of customer account receivable.